Vlog Youtube untuk Meningkatkan Keterampilan Berbicara Peserta Didik SMP Pada Materi Teks Tanggapan Kritis - Budiartati, Agung; Siswanto, Romi (SCAD Independent, 2025)
Speaking skills as language skills that can be developed with the youtube vlog media. The purpose of the learning innovation work